PENGARUH PENERAPAN MEDIA MANIPULATIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Marsinah, Marsinah; Kresnadi, Hery; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this reasearch is to investigate whether or not the use of â€œManipulative Mediaâ€ effective toward the studentsâ€™ achievement in learning mathematic on the third grade students of state elementary schools 37 Southeast Pontianak. This research applied a quasi-experimental design. The population of this research was III B as the experimental group and III A as the control group which tottaly consist of 62 students. The research findings showed that the score of III B was 82.69, while III A got 72.27. Based on the measurement parametricÂ statistic, the result of t-test (2.871) > t-table (1.671). Thus, the alternative hypothesis (Ha) was accepted. Based on the analyse, there is a difference mean score of studentsâ€™ achievement between using pictures and using manipulative media. The effectiveness of manipulative media towards the studentsâ€™ achievement in mathematicÂ on third grade was 0,73 which categorized as high.Â Keywords: Effect, Manipulative Media, Studentsâ€™ Achievment in Mathematic